Effect of Static Magnetic Field on the Efficiency of Granular Sludge Development for Pharmaceutical Wastewater Treatment - Omar, Ahmad Hanis (International Journal of Integrated Engineering, 2019)
The effect of static magnetic field (SMF) on the development of granular sludge was evaluated in sequential batch reactor (SBR) system under alternating aerobic and anaerobic condition fed with pharmaceutical wastewater which is categorized as a high strength wastewater. The magnetic field intensity used in this research was 20 mT and compared with the control system without magnetic field exposure. The results showed that sludge granulation was enhanced significantly in the presence of magnetic field which made the reaction time for granulation process faster compared with that of the control. Matured, dense and compact granules with diameter of 6.5 Â± 1.0 mm with maximum size reaching up to 8.9 mm were developed with good settling velocity of 76.92 m/h. Magnetic field could stimulated EPS production by accumulating iron, calcium and magnesium compounds in the sludge. The contents of total EPS in R2 (with SMF) were 28.5 mg/gVSS, while in R1 (without SMF) were 21.7 mg/gVSS. The magnetic field system was efficiently treated COD, TP, orthophosphate, TN, nitrate and nitrite with over 90% removal from pharmaceutical wastewater. The application of magnetic field is then helpful and reliable for accelerating the granulation process and is capable in treating the pharmaceutical wastewater